The Translation of the Holy Quran - Assistant Prof. Dr.Sanaa Aluey Abdul Sada; Dr. Sanaa Khudhair Mohammed al-Jaberi; Prof. Rafid Sabah al-Tamimi (Genius Journals, 2024)
The translation of the Holy Quran is an interpretation of the Quranic meanings into languages other than Arabic so that it can be understood and its meanings comprehended. The Quran has been translated into most of the world's languages, including European, Asian, African, and Persian. The translation of the Quran has gone through several stages until it stabilized. As for its ruling, there is a difference of opinion among scholars, but the prevailing view is that the translation of the Quran is desirable so that the Quranic message can reach the entire world and this religion can be conveyed to the farthest corners of the earth. It is also considered one of the collective obligations (fard kifaya) that the Muslim community must undertake, as it is a means of conveying the religion to all of humanity. The topic of translation is a very important and sensitive one. After reviewing some reliable sources and references due to its great significance, it has become apparent that the enemies of Islam seek to exploit the translation and interpretation of the Quran's meanings to distort, misinterpret, and conceal the truth. Therefore, we have presented translation, its types, its challenges, the principles upon which it is based, and the opinions and views of scholars from all Islamic schools of thought.
Keywords: Translation; Quran